Pompholyx-like eruptions induced by penicillamine in a patient with wilson's disease - Diana Elizabeth Devassy; Sujata Raj Harshad; Harshad Devarbhai (Wolters Kluwer Medknow Publications, 2019)
Wilson's disease is an inherited disorder of copper metabolism that results in excessive accumulation of copper in various organs, with liver being the primary site of involvement. D-penicillamine (DPA) as a chelating agent forms the mainstay of therapy; however, it can cause a myriad of adverse effects on long-term use. The major adverse effects reported with DPA include disorders of collagen synthesis, such as pseudoxanthoma elasticum-like lesions, autoimmune blistering diseases, and urticarial lesions. Here, we report a young girl who developed extensive pompholyx-like blisters within a few months of starting DPA which on histopathology showed a spongiotic reaction. The lesions improved on stopping DPA and initiation of oral steroids.